A Halloween gene shadow is a potential target for RNA‐interference‐based pest management in the small brown planthopper Laodelphax striatellus. Issue 2 (14th April 2014) - Wan, Pin‐Jun; Jia, Shuang; Li, Na; Fan, Jin‐Mei; Li, Guo‐Qing
Abstract BACKGROUND L aodelphax striatellus is an economically important rice pest in China. Ecdysteroid hormone 20‐hydroxyecdysone regulates insect development and reproduction. The cytochrome P450 monooxygenase Shadow (Sad) plays a critical role in ecdysteroidogenesis. Here, tests were conducted to establish whether Lssad was a potential target gene for RNA‐interference‐based management of L. striatellus. RESULTS L ssad was cloned and characterised. LsSad had Helix‐C, Helix‐I, Helix‐K, PERF and haem‐binding motifs. Lssad is expressed at a higher level in the thorax, where prothoracic glands are located, compared with the level in the head or abdomen. It showed two expression peaks in day 2 and day 4–5 fourth‐instar nymphs, and two troughs in day 1 fourth and fifth instars. Oral delivery of double‐stranded RNA (dsRNA) of Lssad at the nymph stage successfully knocked down the expression of the target gene, reduced the expression level of ecdysone receptor (LsEcR) gene, caused nymphal lethality and delayed development in a dose‐dependent manner. Ingestion of 20‐hydroxyecdysone in Lssad‐dsRNA‐exposed nymphs did not increase Lssad expression level, but almost completely rescued the LsEcR mRNA level and relieved the negative effects on survival and development. CONCLUSIONS The ecdysteroidogenic pathway is conserved in L. striatellus. Lssad can serve as a possible target for dsRNA‐based pesticides for planthopper control. © 2014 Society of Chemical Industry